2007
DOI: 10.1016/j.trstmh.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalences and local variation of human and livestock brucellosis in two villages in Gharbia Governorate, Egypt

Abstract: SummaryThis study aimed at assessing the epidemiology of brucellosis among both human and livestock populations in an endemic area in Egypt. A cross-sectional survey was conducted in two villages, where 616 inhabitants (aged 3-75 years) and 350 livestock of 97 households were enrolled. Sera were tested for Brucella spp. antibodies by tube agglutination test for both populations. Proportions of seropositive sera were 0.0 and 1.7% among the inhabitants, and 0.0 and 16% among livestock of villages I and II, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 7 publications
(13 reference statements)
6
24
1
Order By: Relevance
“…Three incidence studies did not describe the diagnostic tests used but were included because they filled gaps in available data and had otherwise well-documented methods and results [15], [17], [20]. Seroprevalence data were presented in fourteen articles, from surveys conducted in communities [22][28] or from blood donor screening [29]–[32]. Due to a lack of data, several studies focusing on specific sub-groups of the general population where also included: two studies of nomadic communities [33], [34] and one of school children [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three incidence studies did not describe the diagnostic tests used but were included because they filled gaps in available data and had otherwise well-documented methods and results [15], [17], [20]. Seroprevalence data were presented in fourteen articles, from surveys conducted in communities [22][28] or from blood donor screening [29]–[32]. Due to a lack of data, several studies focusing on specific sub-groups of the general population where also included: two studies of nomadic communities [33], [34] and one of school children [35].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of Quality 1 and 2 were only available for 15 countries from the following GBD geographic regions: Northern African and Middle East (17 studies) [8][11], [14], [16], [18], [19], [22], [25]–[27], [30], [32], [34]–[36], Western Europe (8 studies) [12],[13],[17],[20],[21],[23],[24],[28], South and Central America (2 studies) [29],[31], Sub-Saharan Africa (1 study) [33] and North America (1 study) [15], as shown in Figure 2. One additional Quality 1 seroprevalence study from Central Asia [7] was identified through targeted non-systematic searching which, although not fulfilling the publication date criteria of the systematic review, was included in data analysis because it provided otherwise missing data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellosis is an occupationally-associated disease and reports from different parts of the world have shown that one of the high risk groups for brucellosis are livestock farmers Bamaiyi 2016;El Sherbini et al 2007;Jama'ayah et al 2011). The findings in this study showed that farmers had a higher seroprevalence of brucellosis than veterinary technical staff which may due to the better preventive and precautionary measures usually taken by veterinary staff when handling animals based on their knowledge of routes of transmission of disease.…”
Section: Discussionmentioning
confidence: 99%
“…16 The livestock composition of previous, similar studies was heterogeneous, including cattle, goats, sheep, and camels, among others; and found no clear association with unpasteurized milk consumption. 5,13,17,18 The complex dynamics in this kind of setting prevent studies from signaling a single source of infection. Conversely, in our study there was exclusive presence of bovine livestock, suggesting that close contact with infected cattle tissue is a strong associated factor.…”
Section: Discussionmentioning
confidence: 99%